THE IMPACT OF EMPLOYEE SATISFACTION ON THE TOURIST SATISFACTION WITH THE SERVICES OF SPA TOURISM - Goran Perić; Marko Gašić; Marija Stojiljković; Ivana Nešić (Ekonomika Poljoprivrede (1979), 2018)
The quality of employees work in the tourism industry depends primarily on their job satisfaction. This has directed the subject of the research in this paper to examine the impact of employee satisfaction on tourist satisfaction with the services of spa tourism in the Republic of Serbia. Research was conducted using the survey method, the questionnaire technique, in Lukovska Spa, based on a sample of 125 respondents, of which 55 were employees and 70 tourists / guests in hotels "Jelak" and "Kopaonik". The most important fnding of the research is related to the correlation between the employee satisfaction and the tourist satisfaction with the quality of service in Lukovska Spa, which confrmed the hypothesis of the direct and positive impact of employee satisfaction on the tourist satisfaction with the quality of services. Employee satisfaction has a positive impact on the quality of the service, which directly affects the tourist satisfaction with the quality of the services provided.